An exploration of the handling of grammatical structures by Limpopo Province EFAL teachers in FET Phase - Mashiane, Mmetlane Valery (My University, 2019)
This study explores the handling of grammatical structures by the Limpopo Province (LP) English First Additional Language (EFAL) teachers in the Further Education and Training (FET) phase. The problem is that the majority of English language learners’ language proficiency and accuracy are not at an acceptable level. This problem also brings into close scrutiny, the quality of teaching and learning that takes place in English language classrooms, and in particular, the effectiveness of teaching grammar structures in EFAL. The research design was exploratory and the approach was qualitative. A selected number of EFAL FET grammar teachers and English Language Curriculum Advisors (ELCAs) in the LP participated in the study. The study was underpinned by an integration of Behaviourism, Mentalism, Cognitive, and Universal Grammar theories. The study findings indicate some learner language interlanguage and grammar permeability, as well as inadequate handling of grammar knowledge and grammar learning assessment.
Thesis (M. A. (English Studies)) -- University of Limpopo, 2019
Keywords: Grammar; English first additional language; Teachers; Further Education and Training; English language learners; English teachers -- South Africa -- Limpopo; English language -- Grammar -- Study and teaching; English language -- Study and teaching -- South Africa -- Foreign speakers; Grammar, Comparative and general